The Relationship Between Students’ Anxiety Level And English-Speaking Competency In Eleventh-Grade Student Of Sma Negeri 1 Singaraja - Ketut Ivan Yuda Aditya; Luh Gede Eka Wahyuni; Gede Mahendrayana (English Language Education Department, Universitas Majalengka, 2024)
This research investigates the connection between anxiety and English-speaking proficiency among eleventh-grade students at SMA N 1 Singaraja. The objectives of the study are to (1) ascertain the presence of a correlation between the students' anxiety levels and their English-speaking abilities, (2) identify the direction of this correlation, and (3) assess the strength of the correlation between these variables. Employing a correlational design, the study sampled 114 eleventh-grade students through simple random sampling to ensure a balanced representation across the school's three departments. A simple correlation method was used to analyze the data. The findings indicate a significant correlation between students' anxiety levels and their English-speaking competence, with a p-value of .000, which is below the standard significance level of 0.05. The correlation coefficient of -0.378 indicates a low but negative relationship between the variables. Practically, this means that as students' anxiety decreases, their English-speaking competence improves. These results underscore the importance of addressing anxiety in educational settings to enhance students' language performance potentially. Understanding the nature and impact of this relationship can help educators better support students in developing their English-speaking skills.